Inflammatory Mediator Expression Associated With Antibody Response Induced by Live Attenuated vs Inactivated Influenza Virus Vaccine in Children. (24th October 2018) - Martin, Judith M; Avula, Raghunandan; Nowalk, Mary Patricia; Lin, Chyongchiou Jeng; Horne, William T; Chandran, Uma R; Nagg, Jennifer P; Zimmerman, Richard K; Cole, Kelly S; Alcorn, John F
Abstract: Background: The reasons for differences in vaccine effectiveness between live attenuated influenza vaccine (LAIV) and inactivated influenza vaccine (IIV) are not clear. Methods: Blood samples were obtained before vaccination and at days 7 and 21 postvaccination with 2015–2016 quadrivalent IIV or LAIV. Serologic response to the vaccine was measured by hemagglutination inhibition assay. Targeted RNA sequencing and serum cytokine analysis were performed. Paired analyses were used to determine gene expression and were compared between IIV and LAIV recipients. Classification And Regression Trees analysis (CART) identified the strongest associations with vaccine response. Results: Forty-six enrollees received IIV, and 25 received LAIV. The mean age was 11.5 (±3.7) years. Seroconversion with IIV was associated with changes in expression of PRKRA and IFI6 . Nonseroconversion for both IIV and LAIV was characterized by increased interferon-stimulated gene expression. Seroprotection with both vaccines was associated with altered expression of CXCL2 and CD36 . For LAIV, CART showed that changes in expression of CD80, CXCL2, and CASP1 were associated with seroprotection. Serum cytokines showed that IIV seroconversion was associated with decreased CCL3. LAIV seroprotection tracked with decreased tumor necrosis factor–α and interferon-γ. Conclusions: Distinct markers of seroconversion and seroprotection against IIV and LAIV were identified using immunophenotyping and CART analysis.